Spirituality As a Somatic Symptom Intervention: A Systematic Review of University Students’ Wellbeing - Syahrul Hidayat Putra Baso; Muhammad Ihsan Prahasta (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Somatic symptoms such as headaches or indigestion in university students are serious problems that often exacerbate mental health deterioration and impair academic performance. Unfortunately, non-pharmacological interventions such as spiritual approaches are still rarely considered as practical solutions. Despite numerous studies attesting to the link between spirituality and physical health, there has been no systematic synthesis of research in the past 5 years (2020-2025) that addresses how spiritual practices, such as meditation or religious rituals, can mechanistically reduce these symptoms, especially among culturally diverse university students. This systematic review addresses this gap by analyzing multiple studies from Scopus, PubMed, Science Direct, and Proquest selected through PRISMA guidelines after screening 4.132 articles. Inclusion criteria focused on studies that measured the impact of spirituality on university students' somatic symptoms, rather than on mental health in general. Systematic review revealed three key findings: (1) Mindfulness-based spiritual practices (e.g., yoga, prayer) lower biological stress markers (e.g., cortisol), directly alleviating symptoms through mind-body integration; (2) Group spiritual rituals (e.g., congregational meditation) are more effective in non-Western contexts, emphasizing cultural alignment; and (3) Long-term spiritual engagement enhances physical resilience, whereas brief interventions yield only temporary relief. Notably, stable spirituality rooted in strong beliefs reduced physiological stress responses, while uncertain spiritual exploration exacerbated symptoms. Cross-cultural studies highlighted spirituality’s role in boosting positive affect and social support, indirectly mitigating somatic complaints. However, reliance on self-reported data and inconsistent spirituality measurement tools limit causal inferences. This review underscores spirituality’s potential as an adaptive intervention for students’ physical health, contingent on standardized measurement frameworks, culturally sensitive approaches, and longitudinal studies. Universities should prioritize integrating spirituality into holistic well-being programs, fostering both individual practices and community-based rituals to sustain psychophysiological resilience.